Perbandingan Analisis Lendutan Pelat dengan Menggunakan Metode Beam on Elastic Foundation (BoEF) dan Finite Element Method (FEM) - Willis Diana (Semesta Teknika, 2011)
The aim of this study was to compare deflection plates are supported by soil by using the method of Beam on Elastic Foundation (BoEF) and Finite Element Method (FEM). To validated the  methods, used data from laboratory testing of the loading plate models. For the calculation of deflection plates on elastic (soil) foundation, the accuracy of determining the modulus of subgrade reaction will greatly affect the calculation of deflection plate. Deflection calculation used Finite Element Method and BoEF method gave deflections, where close enough to those of experimental result. Both methods can be used to estimate the plate deflection.